Hubungan Antara Motivasi Belajar dan Prestasi Matematika Siswa SDN 01 Malalo - Rahmi, Alfani; Ayu Anastasha, Desti; Safrizal (UNIVERSITAS SERAMBI MEKKAH, 2025)
The purpose of this study was to determine how math learning success and learning motivation relate to each other among students of SD Negeri 01 Malalo. This kind of research is experimental in nature. Under controlled circumstances, experimental research is a technique used to investigate how certain therapies affect others. Qualitative and quantitative methods were used in this study. Data on student learning achievement was obtained from test results, while data on student learning motivation was collected through a motivation questionnaire. Time Series design is the design used in this study. The sample of this study consisted of 27 students from class V A, while the population of this study consisted of 105 students of class V SD Negeri 01 Malalo. The questionnaire method and the test method were used as data collection procedures in this study. Test sheets and questionnaires serve as research tools. Based on the research results, students' learning motivation (X) and math learning achievement (Y) are positively and significantly correlated. The relationship between learning desire and arithmetic learning achievement is shown by the findings of the data analysis, which resulted in r table and r calculated values of 0.381 and 0.388 for an error rate of 5% with n = 27. Given the price ????ℎ???????????????????? > ???????????????????????? (0.388 > 0.381), it can be said that learning motivation and math learning achievement have a positive and significant relationship of 0.388.